Inflammatory and metabolic biomarkers and risk of liver and biliary tract cancer. - Aleksandrova, K; Boeing, H; Nöthlings, U; Jenab, M; Fedirko, V; Kaaks, R; Lukanova, A; Trichopoulou, A; Trichopoulos, D; Boffetta, P; Trepo, E; Westhpal, S; et al. (2014)
UNLABELLED: Obesity and associated metabolic disorders have been implicated in liver carcinogenesis; however, there are little data on the role of obesity-related biomarkers on liver cancer risk. We studied prospectively the association of inflammatory and metabolic biomarkers with risks of hepatocellular carcinoma (HCC), intrahepatic bile duct (IBD), and gallbladder and biliary tract cancers outside of the liver (GBTC) in a nested case-control study within the European Prospective Investigation into Cancer and Nutrition. Over an average of 7.7 years, 296 participants developed HCC (n=125), GBTC (n=137), or IBD (n=34). Using risk-set sampling, controls were selected in a 2:1 ratio and matched for recruitment center, age, sex, fasting status, and time of blood collection. Baseline serum concentrations of C-reactive protein (CRP), interleukin-6 (IL-6), C-peptide, total high-molecular-weight (HMW) adiponectin, leptin, fetuin-a, and glutamatdehydrogenase (GLDH) were measured, and incidence rate ratios (IRRs) and 95% confidence intervals (CIs) were estimated using conditional logistic regression. After adjustment for lifestyle factors, diabetes, hepatitis infection, and adiposity measures, higher concentrations of CRP, IL-6, C-peptide, and non-HMW adiponectin were associated with higher risk of HCC (IRR per doubling of concentrations=1.22; 95% CI=1.02-1.46; P=0.03; 1.90; 95% CI=1.30-2.77; P=0.001; 2.25; 95% CI=1.43-3.54; P=0.0005; and 2.09; 95% CI=1.19-3.67; P=0.01, respectively). CRP was associated also with risk of GBTC (IRR=1.22; 95% CI=1.05-1.42; P=0.01). GLDH was associated with risks of HCC (IRR=1.62; 95% CI=1.25-2.11; P=0.0003) and IBD (IRR=10.5; 95% CI=2.20-50.90; P=0.003). The continuous net reclassification index was 0.63 for CRP, IL-6, C-peptide, and non-HMW adiponectin and 0.46 for GLDH, indicating good predictive ability of these biomarkers. CONCLUSION: Elevated levels of biomarkers of inflammation and hyperinsulinemia are associated with a higher risk of HCC, independent of obesity and established liver cancer risk factors.